Political Ecology of Forest Governance in Vietnam’s Central Highlands: Land Use Change, Power Relations, and Environmental Policy - Duc, Tran Minh (European Journal of Applied Sciences, 2026)
Changes in land use, migration, and policy changes have all impacted forest governance in Vietnam’s Central Highlands. This study focuses on the political ecology of the region, considering how land-use change, power structures, and institutional politics define access to and control over forest resources and shape policy impacts. In Dak Lak, Gia Lai, and Kon Tum provinces, I adopted a multi-scalar and mixed-methods research design, which included household surveys, semi-structured interviews, focus group discussions, and policy document reviews to examine how actors interact within the forest governance system. Findings suggest that land-use change, particularly the expansion of rubber and coffee plantations, hydropower development, and conservation initiatives, has reconfigured forested areas and restricted informal access to forests and land. These changes are attributed to the power structures of state actors, private capital, migrating farmers, and indigenous populations, resulting in disadvantages in forest governance and the allocation of forest benefits. Environmental policies, in particular the Payments for Forest Environmental Services (PFES), have increased income and conservation awareness, but remain limited by unequal participation opportunities, low financial incentives, and persistent tenure insecurity. The study, by combining political ecology with access theory, shows that the outcomes of forest governance are conditioned by political, economic, and institutional structures, rather than formal policies alone. The author suggests that governance structures that are more inclusive and that integrate these elements into policy design are likely to be more effective.